THE EFFECT OF PSYCHOGRAPHIC LIFESTYLE ON PURCHASE DECISIONS AT HANGING CAFES IN SOUTHWEST ACEH DISTRICT - Edyansyah, T; Ahyar, Juni; Ilham, Rico Nur; Chalirafi, Chalirafi; Sullaida, Sullaida (LPPM STIE Muhammadiah Bandung, 2022)
The purpose of this study was to identify and analyze the effect of interest, opinion and activity on purchasing decisions at Cafe Hangouts in Aceh Barat Daya District. The object of this research is a psychographic lifestyle which includes interest, opinion and activity and purchasing decisions at Hangout cafes. The sample selection in this study was based on proportional random sampling, in this study 100 customers were selected who had visited the Nongkrong Cafe, Southwest Aceh. The analysis used in this research was multiple linear regression analysis. The results of this study indicate that partially interest and opinion have a positive effect. and significant to the Purchase Decision at the Cafe Hanging out in Southwest Aceh Regency. The results of this study indicate that partially activity has a positive and insignificant effect on purchasing decisions at Hanging Cafes in Southwest Aceh Regency. The results of this study indicate that the variables of interest, opinion and activity have a positive and significant effect on purchasing decisions at the Nongkrong Cafe, Southwest Aceh Regency.